Biodegradable hydrogels and microbial consortia as a treatment for soil dysbiosis - Davis, Renee A.; Mafune, Korena K.; Winkler, Mari K. H. (Frontiers in Microbiology, 2025)
Terrestrial microbial communities drive many soil processes and can be pushed into a state of dysbiosis upon disturbance. This dysregulation negatively impacts soil biogeochemical cycles, which threatens plant and soil health. Effective treatment of soil dysbiosis requires simultaneous restoration of multiple system components, addressing both the physical structure of soil and its microbial communities. Hydrogels with microbial consortia simultaneously remedy soil hydrodynamics while promoting microbial reestablishment. The purpose of this review is to shed light on soil management practices through the lens of soil dysbiosis. This is important to address not only for soil health and crop productivity, but also to mitigate climate change through improved soil carbon sequestration and reduced greenhouse gas emissions. This review positions hydrogels and microbes as tools for the treatment of soil dysbiosis, contributing to agricultural and climate resilience.